Institutional Framework for Protecting Communal Land Rights in Customary Villages (The Case Study of Pengastulan and Sumberklampok, Bali, Indonesia) - I Nyoman Alit Badrika; I Ketut Mastika; Agus Trihartono; Suji Suji; I Wayan Madra Suartana (Smart Society, 2026)
Communal land rights in Bali face increasing threats from land commercialization, tourism development, and legal uncertainties, highlighting the need for robust governance mechanisms that integrate formal state regulations and customary institutions. This study examines how these institutional systems interact to protect communal land rights in Pengastulan and Sumberklampok villages. Using Scott's four-pillar institutional framework, we conducted a qualitative constructivist study involving 26 informants, including customary leaders, government officials, and community members, through in-depth interviews, participant observation, and document analysis. Results show contrasting institutional capacities: Pengastulan exhibits strong customary legitimacy, cohesive social norms, and resilient cultural practices, but faces pressures from privatization and tourism; Sumberklampok demonstrates weaker customary institutions, relying more on legal advocacy and collective mobilization due to prolonged agrarian conflicts. Findings indicate that effective communal land protection depends on the dynamic interplay of regulatory, normative, cultural-cognitive, and habitual dimensions rather than formal legal recognition alone. The study contributes theoretically by extending institutional governance frameworks to customary land contexts under legal pluralism and offers practical insights for adaptive, collaborative approaches that integrate state administration with local customary mechanisms to strengthen communal land resilience.